Revenue policing, social control, and neoliberalism - Graulich, Nathaniel (2020)
A variety of studies have examined the role of economic structures in policing. These inquiries offer insight into revenue-based law enforcement activities but are simultaneously limited by blind spots in theorization. Reviewing these studies, it is apparent the criminal justice system can and is used to gain revenue for a multitude of public and private organizations. Furthermore, it is clear this is not a new phenomenon in the United States. Nor is the disparate impact of criminal justice activity on segments of U.S. society such as poor or homeless citizens, minority populations including black and latinx populations, and LGBTQ+ communities. Despite these findings, there has been little attention put on how the role of capital in policing and the disparate impacts of policing on populations in the U.S. may be connected and further how tiered justice outcomes may be a design element of America’s policing structure. As such, most of the research to date has not examined how revenue-focused criminal justice processes intentionally or unintentionally impact citizens. When research has examined these aspects there has been disagreement about where the motivation to engage in revenue-based policing activity originates. While several studies point to uncontrollable economic downturn to explain shifts in criminal justice institutions, many factors were left out when researchers came to these conclusions. This leaves relevant elements inadequately explored and limits the external validity of findings. While these studies have been able to capture evidence of rises in reported use of policing for profit, theoretical assumptions in these works led to methodological issues that limit findings and need to be examined using alternative methodology